2017
DOI: 10.25518/1780-4507.13613
|View full text |Cite
|
Sign up to set email alerts
|

Removal of acorns of the alien oak Quercus rubra on the ground by scatter-hoarding animals in Belgian forests

Abstract: Description of the subject. Quercus rubra L. is considered an invasive species in several European countries. However, little is known about its dispersal in the introduced range. Objectives. We investigated the significance of animal dispersal of Q. rubra acorns on the ground by vertebrates in its introduced range, and identified the animal species involved. Method. During two consecutive autumns, the removal of acorns from Q. rubra and from a native oak was assessed weekly in forest sites in Belgium. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Liebl. (sessile oak), in the northern mountains of the Iberian Peninsula where the common vole originally lived, Q. suber L. (cork oak) in Salamanca (Spain), and Q. rubra L (American oak) (Bieberich et al 2016;Merceron et al 2017) in experimental reforestations in Galicia (Spain). The only non-native species is Quercus.…”
Section: Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Liebl. (sessile oak), in the northern mountains of the Iberian Peninsula where the common vole originally lived, Q. suber L. (cork oak) in Salamanca (Spain), and Q. rubra L (American oak) (Bieberich et al 2016;Merceron et al 2017) in experimental reforestations in Galicia (Spain). The only non-native species is Quercus.…”
Section: Study Systemmentioning
confidence: 99%
“…Rubra. We have chosen this species to test its integration in this system of relationships between rodents and oaks if it can adapt to the existing dispersal mechanisms in the area (Bieberich et al 2016;Merceron et al 2017).…”
Section: Study Systemmentioning
confidence: 99%
“…Larger seeds deliver more resources at the early stages of seedling development but they do not necessarily buffer young plants from the negative effects of environmental variation (e.g., from limitations in nutrients or water) or competition of other plants (Jevon et al., 2021 ). However, larger acorns are attractive to seed consumers, so they can be more threatened by acorn predators (Buckley et al., 2006 ; Crawley, 2000 ; Merceron et al., 2017 ; Mezquida et al., 2021 ; Myczko et al., 2017 ). On the other hand, large‐sized seeds are often only partially damaged, so they still preserve the ability to germinate and produce viable seedlings (Branco et al., 2002 ; Hopper et al., 1985 ; Steele et al., 1993 ; Yi & Yang, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Q. frainetto Ten. (Hungarian oak), Q. robur L. (Common oak) and Q. rubra L (American oak)(Bieberich et al 2016;Merceron et al 2017) they are not originally found in the distribution area of Algerian mouse. Q. robur does occur in the Iberian Peninsula, but in the northern mountains where Algerian mouse does not reach.…”
mentioning
confidence: 99%
“…Q. frainetto, and Q. rubra have recently been introduced as ornamental species. We have chosen these two species to test its integration in this system of relationships between rodents and oaks if it can adapt to the existing dispersal mechanisms in the area(Bieberich et al 2016;Merceron et al 2017).…”
mentioning
confidence: 99%